âBRAINWASHING MOTIVASI" TEKNIK MINIMALISASI PENGEMIS DENGAN MAKSIMALISASI POTENSI DAN MOTIVASI MELALUI KONSEP BRAINWASHING - Nabila, Fairuzia Nisa; Huslita, Febtriana; Nesfiawati, Resty; Kusumasari, Herdyani; Mardini, Hikmah (Program Kreativitas Mahasiswa - Gagasan Tertulis, 2013)
The increasing percentage of beggarâs existence has forced our government to take efforts to solve it, but so far all are failed. Concerning to that, we introduce the Brainwashing Motivation (BM) that can be tried as an alternative solution. Inspired by the Social-Learning theory by Bandura, a psychologist, BM is applied in the form of motivation seminars in which some trainings of many kinds of skills with an intensive assistance will be held. BM wonât only be able to reduce the beggarsâ passion to beg, but also give them a lift to live a better life as they own valuable skills.